Efficiency Analysis of Islamic Life Insurance and Islamic General Insurance with Data Envelopment Analysis (DEA) Approach 2017-2022 - Karlita Anggini; Rizky Ayu Puspita; Siti Nur Alfiana Ginting (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2024)
The Islamic insurance industry in Indonesia has yet to reach stability. There are still numerous issues to be addressed on both the demand and supply sides. An efficiency study is required to establish the extent to which Islamic insurance companies may optimize their resource use and have a significant impact on Islamic finance in Indonesia. The goal of this study is to evaluate the effectiveness of Islamic Life Insurance and Islamic General Insurance in Indonesia from 2017 to 2022. The purposive sampling strategy was used to acquire the data for this investigation. The approach used is Data Envelopment Analysis (DEA) with VRS assumptions. According to the study's findings, Islamic Life Insurance and Islamic General Insurance achieved the maximum level of efficiency (100 percent) between 2017 and 2022. However, PT Asuransi Islam Keluarga Indonesia as Islamic Life Insurance and PT Asuransi Jasindo Syariah as Islamic General Insurance have yet to achieve efficiency. This is because the company's tabarru funds, total assets, operating expenses, and claim expenses still need to be more efficient.